2019
DOI: 10.3390/ma12050788
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Microwave Technique in Continuous Flow Processing of Organophosphorus Chemical Reactions

Abstract: The microwave (MW) technique is an efficient tool in the realization of organic reactions, as well as in the analytical field and in the food industry. The continuous flow approach is of special interest as a promising way to scale-up MW-assisted syntheses. Besides summarizing the batch precedents, this review focuses on the utilization of the MW technique in the continuous-flow realization of organophosphorus transformations. The advantages of the continuous flow technique against the batch accomplishment are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 106 publications
(127 reference statements)
0
19
0
Order By: Relevance
“…α-Hydroxy phosphonate derivatives are of great importance due to their various biological actions and therapeutic applications such as bactericidal [ 5 ], fungicidal [ 6 ], antitumor [ 7 ], and HIV inhibitory activities [ 8 ]. The high interest in this class of compounds has been reflected in numerous publications on their synthesis, modification, and application not only in medical chemistry [ 9 , 10 , 11 , 12 , 13 , 14 ]. It was shown that further functionalization of the hydroxy group has a pivotal impact on the biological activity of the modified α-hydroxy phosphonates.…”
Section: Introductionmentioning
confidence: 99%
“…α-Hydroxy phosphonate derivatives are of great importance due to their various biological actions and therapeutic applications such as bactericidal [ 5 ], fungicidal [ 6 ], antitumor [ 7 ], and HIV inhibitory activities [ 8 ]. The high interest in this class of compounds has been reflected in numerous publications on their synthesis, modification, and application not only in medical chemistry [ 9 , 10 , 11 , 12 , 13 , 14 ]. It was shown that further functionalization of the hydroxy group has a pivotal impact on the biological activity of the modified α-hydroxy phosphonates.…”
Section: Introductionmentioning
confidence: 99%
“…The MW technique proved its significance for enabling faster and more efficient synthesis processes in organic and medicinal chemistry [19]. It is also widely used for the preparation of phosphorus-containing derivatives [20]. In order to decrease the reaction time of the oxidative addition, we studied this transformation under MW conditions.…”
Section: Figure 1 General Structure Of Phosphole Oxides (A) and Benzo[b]phoshole Oxides (B)mentioning
confidence: 99%
“…Microwave (MW) heating coupled to a flow reactor was reported for providing a readily scalable process compared to a conventional batch microwave system. [37] Jansa, Janeba and co-workers developed a batch MW-assisted method for the hydrolysis of acyclic nucleoside phosphonate diesters towards the corresponding…”
Section: Hydrolysis and Transesterification Reactionsmentioning
confidence: 99%